Analisis Keuntungan Usaha Kacang Sangrai “Sindo” Di Desa Kanonang Tiga Kecamatan Kawangkoan Kabupaten Minahasa - Wala, Elsinta Esterlina; Laoh, Esry Olly Harryani; Mandei, Juliana Ruth (AGRI-SOSIOEKONOMI, 2023)
This study aims to analyze the profits from the Sindo Sangria peanut business in Kanonang Tiga Village, Kawangkoan District, Minahasa Regency. This research was conducted in August to October 2022. The method used in this research is the survey method with the types of data consisting of primary data and secondary data. Primary data is data taken directly from the location through interviews with Sindo Roasted Bean business owners using a prepared questionnaire and direct observation at the research site. Secondary data is obtained from literature and literature studies through documents, publications, or research results from various institutions or institutions that support and relate to the required research topic. Based on the results of research conducted on the "Sindo" roasted peanut business regarding the analysis of the profits obtained by the business owner, the conclusion obtained by the researcher is that the "Sindo" roasted peanut business earns a profit of IDR20,619,110 in 6 days of production process activities. R/C Ratio analysis is 2.31 which means that this business is profitable and can be maintained.